Building A Semantic-Primitive-Based Lexical Consultation System. - Lim, Beng Tat; Tang, Dr ,Enya Kong; Guo, Dr ,Cheng Ming (2003)
The paper describes the design of semantic primitive-based lexical consultation system and the possible processes which will be performed on a machine-readable dictionary (MRD) and corpus to produce a machine-tractable dictionary.